50 people every Christian should know : learning from spiritual giants of the faith - Wiersbe, Warren W. (Grand Rapids, MI : Baker Books, 2009)
Christians in the twenty-first century need encouragement and inspiration to lead lives that honor God. When faith is weak or the pressures of the world seem overwhelming, remembering the great men and women of the past can inspire us to renewed strength and purpose. Our spiritual struggles are not new, and the stories of those who have gone before us can help lead the way to our own victories. 50 People Every Christian Should Know gives a glimpse into the lives of such people as Charles H. Spurgeon, G. Campbell Morgan, A.W. Tozer, Fanny Crosby, Amy Carmichael, Jonathan Edwards, James Hudson Taylor, and many more.
Katherine von Bora (1499/1552) -- Samuel Rutherford (1600/1661) -- Matthew Henry (1662/1712) -- Jonathan Edwards (1703/1758) -- George Whitefield (1714/1770) -- Charles Simeon (1759/1836) -- Christmas Evans (1766/1838) -- John Henry Newman (1801/1890) -- Richard Trench (1807/1886) -- Andrew Bonar (1810/1892) -- Robert Murray McCheyne (1813/1843) -- F.W. Robertson (1816/1853) -- John Charles Ryle (1816/1900) -- Fanny Crosby (1820/1915) -- Alexander MacLaren (1826/1910) -- J.B. Lightfoot (1828/1889) -- R.W. Dale (1829/1895) -- Joseph Parker (1830/1902) -- J. Hudson Taylor (1832/1905) -- Charles H. Spurgeon (1834/1892) -- Phillips Brooks (1835/1893) -- Frances Ridley Havergal (1836/1879) -- Dwight I. Moody (1837/1899) -- George Matheson (1842/1906) -- Henry Drummond (1851/1897) -- R.A. Torrey (1856/1928) -- Alexander Whyte (1836/1921) -- C.I. Schofield (1843/1921) -- F.B. Meyer (1847/1929) -- W. Robertson Nicoll (1851/1923) -- Thomas Spurgeon (1856/1917) -- Samuel Chadwick (1860/1932) -- Charles E. Jefferson (1860/1937) -- W.H. Griffith Tthomas (1861/1924) -- A.C. Gaebelein (1861/1945) -- B.J. Carroll (1843/1914) -- G. Campbell Morgan (1863/1945) -- John Henry Jowett (1864/1923) -- J.D. Jones (1865/1942) -- George H. Morrison (1866/1928) -- Amy Carmichael (1867/1951) -- Frank W. Boreham (1871/1959) -- Joseph W. Kemp (1872/1933) -- Oswald Chambers (1874/1917) -- H.A. Ironside (1876/1951) -- Clarence Edward MaCartney (1879/1957) -- William Whiting Borden (1887/1913) -- Alva Jay McClain (1888/1968) -- A.W. Tozer (1897/1963) -- W.E. Sangster (1900/1960) -- William Culbertson (1905/1971).
Includes bibliographical references (pages 381-398).
Previously published as two separate titles : Living with the giants, 1993 and Victorious Christians you should know, 1984.
Keywords: Christian biography